(Full) Employment Policy: Theory and Practice - Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 1998)
Although the U.S. unemployment rate in 1998 was at its lowest level since the late 1960s, the nation's employment problem is still far from solved. Although many economists assume that unemployment tends toward a natural rate below which it cannot go without creating inflation, this paper asks whether the current employment levels are the best that can be achieved in times of prosperity and whether current employment policies will be able to deal with the challenges of the next downturn. To evaluate these questions, the author examines the relative merits of three proposed strategies to improve the employment situation-a reduced workweek, employment subsidies, and a public service job opportunity program-to see if they will meet the challenges of upholding an individual's basic right to job while not stimulating inflation. He finds that a shorter workweek and wage subsidies both have failed to meet one or both of these challenges, but that a public service job opportunity program, such as the "employer of last resort policy," would satisfy both the full employment and noninflationary criteria.
Keywords: 330